2022
DOI: 10.1371/journal.pone.0277368
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on the impact of the COVID-19 pandemic on psychological outcomes: Multiple indicators and multiple causes modeling

Abstract: Although the psychological impact of coronavirus disease 2019 (COVID-19) has been evaluated in the literature, further research is needed, particularly on post-traumatic stress disorder (PTSD) and psychological outcomes, is needed. This study aims to investigate the effect of the COVID-19 pandemic on psychological outcomes (depression, anxiety, and insomnia). A cross-sectional study using an online survey was conducted using the following instruments: Impact of Event Scale-Revised (IES-R), Patient Health Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 69 publications
(148 reference statements)
0
21
0
Order By: Relevance
“…Therefore, because the present study had a small sample size, we were unable to use advanced psychometric testing (e.g., principal component analysis or confirmatory factor analysis) to examine the factor structure of the newly developed questionnaire in the present study. Specifically, such advanced psychometric testing requires a large sample size of over 200 [ 48 , 103 , 104 , 105 ]. Moreover, with the small sample size in the present study, the internal consistency could only be examined using Cronbach’s alpha, which has a strong assumption of tau equivalence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, because the present study had a small sample size, we were unable to use advanced psychometric testing (e.g., principal component analysis or confirmatory factor analysis) to examine the factor structure of the newly developed questionnaire in the present study. Specifically, such advanced psychometric testing requires a large sample size of over 200 [ 48 , 103 , 104 , 105 ]. Moreover, with the small sample size in the present study, the internal consistency could only be examined using Cronbach’s alpha, which has a strong assumption of tau equivalence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SEM allows for simultaneously estimating a series, but independent, multiple regression equations cannot. It can also incorporate latent variables into the analysis and accounts for measurement errors in the estimation process [ 60 , 61 , 62 , 63 , 64 ]. In other words, SEM is a statistical technique that establishes measurement models and structural models to address complicated behavioral relationships [ 61 , 62 , 65 , 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…It can also incorporate latent variables into the analysis and accounts for measurement errors in the estimation process [ 60 , 61 , 62 , 63 , 64 ]. In other words, SEM is a statistical technique that establishes measurement models and structural models to address complicated behavioral relationships [ 61 , 62 , 65 , 66 ]. Therefore, SEM with the maximum likelihood estimator was used to explore the association between sibling bullying through its two subscales (the victim and the bully) and school bullying (the bullying student and the victim) and the association between parental acceptance–rejection and school bullying.…”
Section: Methodsmentioning
confidence: 99%
“…GAD-7 and PHQ-9 features 7 and 9 questions respectively, with scoring based on the 4-point Likert scale, and both questionnaires are reported to have a good internal consistency (GAD-7 = 0.92, PHQ-9 = 0.89) [29,30]. Participants were required to score each statement on a scale of 0-3, and the total score was calculated and we categorized the students into none (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19) or severe (� 20) depression; and minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), or severe (15)(16)(17)(18)(19)(20)(21) anxiety. Students with a PHQ-9 and GAD-7 score of 4 or less than 4 were categorized as not having any depression or anxiety respectively.…”
Section: Plos Onementioning
confidence: 99%
“…The risk of health outcomes was higher in females and linked to sleep quality, memory difficulties, performance decline, and medium-intensity phone use [10]. Another study that recruited participants from 20 countries found that post-traumatic stress disorder (PTSD) caused by COVID-19 was significantly associated with depression and anxiety; 69% of participants experienced depression, while 57% had anxiety symptoms [11]. During a mere 2 weeks of COVID-19 quarantine, 45% of 530 students in a survey strongly agreed that they felt emotionally detached from their closed ones, and a quarter of them felt depressed [12].…”
Section: Introductionmentioning
confidence: 99%